PENGARUH MODERASI PROFITABILITAS DARI KEPUTUSAN INVESTASI DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019) - Saputri Devita; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to test the influence of investment decisions and good corporate governance moderated by profitability on the value of the company. Investment decisions are projected using Total Asset Growth, good corporate governance is measured by CGPI score, profitability is measured by return on equity and company value is measured by price book value. The data used in this study is secondary data in the form of annual reports from 2016-2019 obtained from the Website of the Indonesia Stock Exchange or www.idx.co.id. The population in this study amounted to 159 manufacturing companies listed on the Indonesia Stock Exchange with sampling techniques using purposive sampling obtained by 102 companies. Hypothesis testing in this study using logistic regression analysis with the help of SPSS applications. The results obtained indicate that (1) investment decisions does not have a effect on firm value (2) good corporate governance has a significant effect on firm value (3) profitability has a significant positive effect on firm value (4) profitability strengthens the effect of investment decisions on firm value. company (5) profitability is able to moderate the effect of good corporate governance on firm value.Keywords: Investment Decisions, Good Corporate Governance, Profitability, Company Value